c-Fos expression following context conditioning and deep brain stimulation in the bed nucleus of the stria terminalis in rats - Kelly Luyck (Nature Portfolio, 2020)
Abstract Deep brain stimulation (DBS) in the bed nucleus of the stria terminalis (BST), a region implicated in the expression of anxiety, shows promise in psychiatric patients, but its effects throughout the limbic system are largely unknown. In male Wistar rats, we first evaluated the neural signature of contextual fear (N = 16) and next, of the anxiolytic effects of high-frequency electrical stimulation in the BST (N = 31), by means of c-Fos protein expression. In non-operated animals, we found that the left medial anterior BST displayed increased c-Fos expression in anxious (i.e., context-conditioned) versus control subjects. Moreover, control rats showed asymmetric expression in the basolateral amygdala (BLA) (i.e., higher intensities in the right hemisphere), which was absent in anxious animals. The predominant finding in rats receiving bilateral BST stimulation was a striking increase in c-Fos expression throughout much of the left hemisphere, which was not confined to the predefined regions of interest. To conclude, we found evidence for lateralized c-Fos expression during the expression of contextual fear and anxiolytic high-frequency electrical stimulation of the BST, particularly in the medial anterior BST and BLA. In addition, we observed an extensive and unexpected left-sided c-Fos spread following bilateral stimulation in the BST.